2021
DOI: 10.3892/etm.2021.10228
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑145‑5p inhibits hypoxia/reoxygenation‑induced apoptosis in H9c2 cardiomyocytes by targeting ROCK1

Abstract: There is increasing evidence that microRNAs (miRs) play critical roles in the pathological and physiological processes associated with myocardial ischemia reperfusion (I/R). miR-145 has been extensively studied in the cardiovascular system; however, the role of miR-145 in myocardial I/R remains unclear. Therefore, the present study aimed to investigate the role and mechanism of miR-145-5p in myocardial I/R by establishing a hypoxia/reoxygenation (H/R) model using H9c2 cardiomyocytes. The expression of miR-145-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…44 In cardiomyocytes, miR-145-5p overexpression inhibited apoptosis and hypoxia/reoxygenation-induced apoptosis. 45 Overall, based on our findings, we suggest that the effect of miR-145-5p on apoptosis may depending on the differentiation state of each cellular model. Therefore, in the future, research will be conducted to determine the regulatory mode between miR-145-5p and target genes to better understand how miR-145-5p plays role in GPM apoptosis.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…44 In cardiomyocytes, miR-145-5p overexpression inhibited apoptosis and hypoxia/reoxygenation-induced apoptosis. 45 Overall, based on our findings, we suggest that the effect of miR-145-5p on apoptosis may depending on the differentiation state of each cellular model. Therefore, in the future, research will be conducted to determine the regulatory mode between miR-145-5p and target genes to better understand how miR-145-5p plays role in GPM apoptosis.…”
Section: Discussionsupporting
confidence: 54%
“…In contrast, miR‐145 overexpression inhibited oxygen‐glucose deprivation‐induced apoptosis and restored astrocyte health, 42 and inhibited high glucose‐induced apoptosis in podocytes, 43 likewise, the sponge of miR‐145‐5p with KCNQ1OT1 could induce apoptosis in bladder cancer 44 . In cardiomyocytes, miR‐145‐5p overexpression inhibited apoptosis and hypoxia/reoxygenation‐induced apoptosis 45 . Overall, based on our findings, we suggest that the effect of miR‐145‐5p on apoptosis may differ depending on the differentiation state of each cellular model.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, caspase-3 also can cleave ROCK1 at a conserved DETD1113/G sequence, thereby removing the autoinhibitory C-terminal region and resulting in constitutively activation of ROCK1, and high-expression of ROCK1 modulated the apoptosis in many types of cells, 21 , 22 thus we speculated that it might be involved in the compound DBH2 induced apoptosis of K562 cells. Our results showed that compound BDH2 up-regulated the expression of ROCK1 in dose-dependent manner ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that miRNAs play important roles in the pathological processes of cardiomyocyte apoptosis, fibrosis and hypertrophy following myocardial infarction. For example, the overexpression of miR-145-5p was demonstrated to inhibit hypoxia/reoxygenation-induced cardiomyocyte apoptosis, alleviate myocardial ischemia/reperfusion injury and exert cardioprotective effects (33). In addition, miRNA-214 was found to be highly expressed in the serum of elderly patients with AMI, and inhibited the apoptosis of human cardiomyocytes, indicating that miRNA-214 contributes to myocardial infarction (34).…”
Section: Discussionmentioning
confidence: 99%